Therapeutic Communities and the (re)emergence of asylums in Rio de Janeiro - Passos, Rachel Gouveia; Souza de Farias, Jessica; Meyre da Silva Gomes, Tathiana; de Castro Lopes de Araujo, Giulia (Argumentum, 2020)
Currently, actions directed toward those who abuse alcohol and other drugs are applied from a moralising perspective. One that blames the individual and, as a solution, demands the control of the body from a religious standpoint, associating mental healthcare with self-control and faith. This article aims to relate increases in financial incentives for therapeutic communities to the recent history of the situation and questions the implications for the implementation of the National Policy on Mental Health, Alcohol and Drugs in the municipality of Rio de Janeiro, from 2017 onwards.